Boundaries of Social Capital in Entrepreneurship - Light, Ivan; Dana, Léo–Paul (Entrepreneurship Theory and Practice, 2013)
Our research begins with a theoretical critique of the social capital literature, and then focuses on Old Harbor, Alaska. In this remote outpost, mainly populated by Alutiiq people, all entrepreneurs self–identified as Euro–Americans or multi–ethnic, not Alutiiq. Although Alutiiq people have abundant social capital, which they employed for economic purposes, they did not employ their social capital for commercial entrepreneurship. Our findings suggest that social capital promotes entrepreneurship only when supportive cultural capital is in place.